2008
DOI: 10.1029/2007jd008983
|View full text |Cite
|
Sign up to set email alerts
|

A reexamination of the QBO period modulation by the solar cycle

Abstract: [1] Using the updated Singapore wind from 1953 to 2007 for the lower stratosphere 70-10 hPa, courtesy of Barbara Naujokat of Free University of Berlin, we examine the variation of the period of the Quasi-Biennial Oscillation (QBO) as a function of height and its modulation in time by the 11-year solar cycle. The analysis is supplemented by the ERA-40 reanalysis up to 1 hPa. Previously, it was reported that the descent of the easterly shear zone tends to stall near 30 hPa during solar minimum, leading to a leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 27 publications
6
37
2
Order By: Relevance
“…This correlation changes sign over ∼ 40 year periods, indicating the change in the QBO period is not directly forced by the solar cycle. This result is in agreement with Fischer and Tung (2008), who analyzed an equatorial zonal wind data set and found that while the QBO period was anticorrelated with the solar cycle during the first three solar cycles, it became positively correlated in the latter three cycles. There is one caveat regarding our internally generated QBO: since the internally generated QBO in the WACCM4 simulations is forced primarily by a parameterization of inertial gravity waves (Xue et al, 2012), the source of the waves is largely deterministic.…”
Section: Summary and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This correlation changes sign over ∼ 40 year periods, indicating the change in the QBO period is not directly forced by the solar cycle. This result is in agreement with Fischer and Tung (2008), who analyzed an equatorial zonal wind data set and found that while the QBO period was anticorrelated with the solar cycle during the first three solar cycles, it became positively correlated in the latter three cycles. There is one caveat regarding our internally generated QBO: since the internally generated QBO in the WACCM4 simulations is forced primarily by a parameterization of inertial gravity waves (Xue et al, 2012), the source of the waves is largely deterministic.…”
Section: Summary and Discussionsupporting
confidence: 81%
“…This change in the period was shorter than the observed 3-6 month variation found in Salby and Callaghan (2000), but larger than the ∼ 1 month variation found in an earlier model study by McCormack (2003). Fischer and Tung (2008), however, provide results from an equatorial zonal wind data set showing that the QBO period was anticorrelated with the solar cycle during the first three solar cycles during this period and positively correlated in the latter three cycles. The modulation of the QBO by the solar cycle remains an open question.…”
contrasting
confidence: 41%
“…In the case of monthly mean ozone data the trend model should, in addition to the constant term and the linear trend, include harmonic terms representing seasonal variations and QBO (quasi-biennial oscillation) frequencies and phases. For instance Fischer and Tung (2008) revealed dominant QBO frequencies during the first decade in this century with periods of 26, 27, 28 and 29 months. Fitting all four nearby frequencies simultaneously may result in undesirable beat frequencies.…”
Section: Trendsmentioning
confidence: 99%
“…Note that the modulation by the solar cycle is nonstationary in time and induces some uncertainty (Hamilton 2002;Fischer and Tung 2008). It is also shown in GCM and chemistry climate model (CCM) studies that simulated QBO-like oscillations change with global warming (Kawatani et al 2011;Shibata and Deushi 2012).…”
Section: Introductionmentioning
confidence: 99%